A High-Density Genetic Linkage Map and Fine Mapping of QTL For Feed Conversion Efficiency in Common Carp (Cyprinus carpio) - Zhang, Xiaofeng; Luan, Peixian; Cao, Dingchen; Hu, Guo (Frontiers in Genetics, 2021)
Feed conversion efficiency (FCE) is an economically crucial trait in fish, however, little genetic and genomic progresses have been made for this trait because of the difficulties in measurement of trait phenotypes. In this study, we constructed a high-density and high-resolution genetic linkage map with 28,416 SNP markers for common carp(Cyprinus carpio) based on high throughput genotyping with the carp 250K single nucleotide polymorphism (SNP) array in full-sib F1 family of mirror carp (Cyprinus carpio) consisting of 141 progenies. The linkage map contained 11,983 distinct loci and spanned 3,590.09cM with an average locus interval of 0.33cM. A total of 17 QTLs for FCE trait were detected on 4 LGs( LG9, LG20, LG28 and LG32), explaining 8.9–15.9% of the phenotypic variations. Several QTLs clustered together at the same linkage group. Nine candidate genes (ACACA, SCAF4, SLC2A5, TNMD, PCDH1, FOXO, AGO1, FFAR3 and ARID1A)underlying feed efficiency trait were also identified, which biological functions may involve in the lipid metabolism, carbohydrate metabolism, energy deposition and fat accumulation, digestion, regulating growth, cell proliferation and differentiation according to GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) annotations. The high density and high-resolution genetic linkage map provides an important tool for QTL fine mapping of economically important traits. Our novel findings provide a basis for elucidating genetic mechanism of feed efficiency and potential marker-assisted selection in common carp.